Economic Adjustment of Default Probabilities - Tomáš Vaněk (European Journal of Business Science and Technology, 2016)
This paper proposes a straightforward and intuitive computational mechanism for the economic adjustment of default probabilities, allowing the extension of the original (usually one-year) probability of default estimates for more than one period ahead. The intensity of economic adjustment can be flexibly modified by setting the appropriate weighting parameter. The proposed mechanism is designed to be useful especially in the context of lifetime expected credit losses calculation within the IFRS 9 requirements.